ANALYSIS OF "TERRITORY BRANDING", EXISTING SHORTCOMINGS AND SOLUTIONS IN IMPROVING THE TOURISTIC IMAGE OF OUR COUNTRY AT THE WORLD LEVEL - Narziqulov Elbek Farxod o’g’li (Scholar Express Journal, 2024)
This article examines the statistical indicators of tourism in our country and today's tourism opportunities, analyzes the marketing and PR work carried out by the tourism committee, analyzes international statistical indicators of tourism, the tourism brand of our country and its existing shortcomings, and presents proposals. An analysis of advertising videos used to create the international image of our country was carried out, as well as an analysis of the types of travelers visiting our country
Keywords: tourism; brand; statistics